Flurbiprofen-induced generalized bullous fixed drug eruption. (January 2014) - Balta, I; Simsek, H; Simsek, GG
Fixed drug eruption (FDE) is an unusual drug-related side effect that results in recurrent lesions whenever the causative drugs are used. FDEs usually occur as a single, sharply demarcated, round erythematous patch or plaque, occasionally with localized bullae. The most common offending agents include antimicrobials, nonsteroidal anti-inflammatory drugs, and antiepileptics. There are some reports where contact dermatitis and cutaneous vasculitis have been associated with the use of flurbiprofen. We present the case of a 50-year-old man with flurbiprofen-induced generalized bullous FDE. To the best of our knowledge, the most serious form of FDE, the generalized bullous FDE, to be caused by flurbiprofen has not been reported previously.